1-(2-aminophenyl)-1H-1, 2, 3-triazole-4-carboxylic acid: activity against Gram-positive and Gram-negative pathogens including Vibrio cholerae. Issue 10 (18th October 2017) - Maji, Krishnendu; Haldar, Debasish
Abstract : We report a new synthetic aromatic ε-amino acid containing a triazole moiety with antimicrobial potential against Gram-positive, Gram-negative and pathogenic bacteria including Vibrio cholerae . Structure–property relationship studies revealed that all the functional groups are essential to enhance the antimicrobial activity. The 1-(2-aminophenyl)-1H-1, 2, 3-triazole-4-carboxylic acid was synthesized by click chemistry. From X-ray crystallography, the amino acid adopts a kink-like structure where the phenyl and triazole rings are perpendicular to each other and the amine and acid groups maintain an angle of 60°. The agar diffusion test shows that the amino acid has significant antibacterial activity. The liquid culture test exhibits that the minimum inhibitory concentration (MIC) value for Bacillus subtilis and Vibrio cholerae is 59.5 µg ml −1 . FE-SEM experiments were performed to study the morphological changes of bacterial shape after treatment with compound 1 . The antimicrobial activity of the amino acid was further studied by DNA binding and degradation study, protein binding, dye-binding assay and morphological analysis. Moreover, the amino acid does not have any harmful effect on eukaryotes.